Poverty and child neglect – the elephant in the room?. (23rd March 2017) - Gupta, Anna
Abstract : There has been much discussion in the past few years about how social workers in England should respond to cases of child neglect, with calls to take more children into care and speed up the process towards adoption. In this article it is argued that current dominant discourse framed in terms of individual pathology disregards the substantial body of knowledge on the effects of poverty and the complex interrelationships between poverty and neglect; perpetuates the blaming of parents; and ultimately fails to serve the interests and promote the rights of many children and their families. Drawing on the capability approach and the work of Lister, the article concludes with an initial exploration of the development of a more sophisticated and multidimensional analysis of poverty and parenting that incorporates both psychological and social causes in ways that challenge the polarisation of the debate on poverty and neglect.